Evaluating downcycling techniques a case study - Ubaldo, Orphelle Lizza M.; Buencamino, Lorena M. (2009.)
This study evaluated existing downcycling techniques useful in the development of an interior accessory product. Downcycling practice in such a way that there is a decrease in the value of the waste materials. Using a case study method, existing processes and technologies recycling residual wastes were investigated. The samples were purposively selected based on its utilization of downcycling techniques or those that do not retain the inherent properties of the materials. Interviews and observations on the organizations and communities performing them were conducted to gather additional information. The first technique involves tile-making using pulverized residual wastes mixed with sand and cement developed by E.A.R.T.H Products Philippines, Inc. and Barangay Bagumbayan, Project 4 Quezon City. The second technique is the recycling of Foamed Polystyrene or Styrofoam which involves melting developed by the Department of Science and Technology-Materials Science Division-Industrial Technology Development Institute (DOST-MS-ITDI) in collaboration with the Polystyrene Packaging Council of the Philippines (PPCP). The third technique is glass recycling which involves melting, glass blowing and lampworking developed by DOST-MS-ITDI. The samples were tabulated and evaluated based on their eco-efficiency compliance. The findings showed that the first technique was the most eco-efficient because it does not involve any melting process. The technique was applied to the development of a detached modular shelving unit. With the incorporation of the technique, design conceptualization, and design paradigm; the product was designed with emphasis to modularity, function, and eco-efficiency. The product is lightweight because it is made of plastic residuals. It is also durable because of the scrap cloth and glass binders in the mixture. However, improvements may still be done on the load bearing capacity for future projects. Related studies on the use of the material for other purposes are recommended. These uses include countertops , moldings, handles, sinks, and interior tiles. the researcher also suggests further studies on the remaining two techniques for eco-efficiency improvements. The results of the study may also b introduced to decorative arts and interior construction classes for further development or application.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Recycling (Waste, etc.) -- Case studies